Tales of the ER-Golgi Frontier: Drosophila-Centric Considerations on Tango1 Function - Feng, Zhi; Yang, Ke; Pastor-Pareja, José C. (Frontiers in Cell and Developmental Biology, 2021)
In the secretory pathway, the transfer of cargo from the ER to the Golgi involves dozens of proteins that localize at specific regions of the ER called ER exit sites (ERES), where cargos are concentrated preceding vesicular transport to the Golgi. Despite many years of research, we are missing crucial details of how this highly dynamic ER-Golgi interface is defined, maintained and functions. Mechanisms allowing secretion of giant cargos such as the very abundant collagens are also poorly understood. In this context, Tango1, discovered in the fruit fly Drosophila and widely conserved in animal evolution, has received a lot of attention in recent years. Tango1, an ERES-localized transmembrane protein, is the single fly member of the MIA/cTAGE family, consisting in humans of TANGO1 and at least 14 different related proteins. After its discovery in flies, a specific role of human TANGO1 in mediating secretion of collagens was reported. However, multiple studies in Drosophila have demonstrated that Tango1 is required for secretion of all cargos. At all ERES, through self-interaction and interactions with other proteins, Tango1 aids ERES maintenance and tethering of post-ER membranes. In this review, we discuss discoveries on Drosophila Tango1 and put them in relation with research on human MIA/cTAGE proteins. In doing so, we aim to offer an integrated view of Tango1 function and the nature of ER-Golgi transport from an evolutionary perspective.